Inhibition of the Growth of Tumors Induced Ehrlich Ascites by Pre-Treatment with Pomegranate and Beetroot Juice in Mice - Dalia I. Hemdan (Pakistan Journal of Medical & Health Sciences, 2022)
The present study was to investigate the antioxidant and antitumor effects of three natural juice (pomegranate, beetroot, and both of them pomegranate and beetroot) injected with Ehrlich ascites carcinoma (EAC) - bearing female mice. The results show that pomegranate and beetroot juice extract is notable sources of phenolic acids and flavonoids. The biological experimental were distributed into six mice groups, the control negative group, and the resultant mice were injected with EAC. The mice were divided into a control EAC positive, group (3) EAC and injected with cisplatin, in addition, the EAC (4, 5, and 6) groups were separately taken orally with pomegranate, beetroot, and both pomegranate and beetroot. The total blood count, hepatic lipid peroxidation index, thiobarbituric acid-reactive substances (TBARS), catalase enzyme activity (CAT), and glutathione peroxidase (GPx) levels were evaluated, as well as liver sections were histopathological examined. In mice harboring EAC, there was a reduction in CAT and GPx activity and an increase in TBARS content. Pomegranate, beetroot, and both pomegranate and beetroot juice treatments improved the complete blood count, the negative changes in the liver enzymes, and the histopathological changes in liver sections. These improvements included increased antioxidant activities, decreased lipid peroxidation, inhibition of EAC cell proliferation, and induction of apoptosis. From the results, it could be concluded that the pomegranate and beetroot had the highest contained phenolic and flavonoid content. As a result, it can prevent the biochemical and histological alterations brought on by EAC without having any negative side effects.